i-Learn portal: The perception among FTMSK students / Norhayati Ishak - Ishak, Norhayati (2006)
The Internet is a technological development that has the potential to change not only the way society retains and accesses knowledge but also to transform and restructure traditional models of higher education, particularly the delivery and interaction in and with course materials and associated resources. Utilizing the Internet to deliver e- Leaming initiatives has created expectations both in the business market and in higher education institutions. Indeed, e-Leaming has enabled universities to expand on their current geographical reach, to capitalize on new prospective students and to establish themselves as global educational providers. Many academic institutions in Malaysia commit themselves to e-leaming because they believe in its effectiveness as an alternative approach to the traditional classroom method of disseminating information. E-leaming on i-Learn portal in UiTM, is an approach to facilitate and enhance e-leaming thru and base on, computer and communications technology. Now i-Leam Portal can be accessed by UiTM lectures, students and staff. This paper review the perception of students on i-Leam portal. Data and information will be obtained from FTMSK students in UiTM Shah Alam. About 200 questionnaires were distributed to the students to obtain feedback. Finding and result from data collection show the students perception, problem that the students face and recommendation that they think can solve their problem on i- Leam Portal. Analysis information that is gathered from the questionnaire determines the parameters of independent variable toward the perception of student on i-Leam Portal.